Tissue culture of Orthosiphon stamineus and effects of abiotic stress exposure on somaclonal variation / Hanisah Ali - Hanisah , Ali (2022)
Orthosiphon stamineus is a medicinal herb that has long been used as a traditional treatment for a variety of ailments and disorders, including cardiovascular disease and epilepsy. In this study, an efficient mircopropagation technique of this species was developed. The plantlets produced were subjected to various stress factors to elucidate the effects of these stresses on the occurrence of somaclonal variation in this species. Murashige and Skoog (MS) media supplemented with 2.0 mg/L kinetin plus 0.5 mg/LIAA has been identified as the optimum in vitro regeneration media (OM) for nodal explant, yielding the highest production of shoots (5.57 ± 0.42) and leaves (20.53 ± 1.91) per explant. The clonal plantlets were subjected to an Inter Simple Sequence Repeat (ISSR) analysis to determine the genetic fidelity of the regenerants. Data analysis confirmed the clonal nature of the resulting plantlets, based on very low polymorphism (7.32%) and low genetic distance values observed in all samples compared to the mother plant. The plantlets were also exposed to various stress factors in different concentration such as high salinity, abscisic acid (ABA) and high cytokinin, by sub-culturing the plantlets onto OM added with various concentrations of NaCl, ABA and high kinetin levels. The exposure to the various stress factors was observed to result in the occurrence of somaclonal variation in O. stamineus, where incidence of hyperhydricity (vitrification) was found to be the most prominent. The variants were then also subjected to an ISSR analysis to compare their genetic distance with the clonal plantlets produced on OM as well as the mother plant. 70.12% polymorphism was discovered in all variants. The results of this study also showed that the plantlets' photosynthetic ability was reduced when the abiotic stress levels increased (as shown by high MDA levels). It was also discovered that when stress levels increased, the chlorophyll content would decrease, which indicates the potential of manipulating the plantlets’ response to stress as a way to increase the production of certain metabolites. Further research should be conducted on the metabolites that are generated and the metabolic pathways related to somaclonal variation, as a result of the exposure to abiotic stress.